Volume 3: 28th Computers and Information in Engineering Conference, Parts a and B 2008
DOI: 10.1115/detc2008-49986
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Hydraulic Mixing Nozzle

Abstract: In industry, mixing tanks are used to homogenize two or more different products that have been combined. This work investigates the use of computational fluid dynamics (CFD) to seek an enhanced design for a hydraulic mixing nozzle. This paper outlines a method for a numerical specification of a nozzle design and generation of a CFD model to analyze it. Characteristics that influence jet distance and trajectory, such as horn size, shape, and entrainment area, are reviewed. The relative importance of each of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The objective function for the shape optimization was to obtain a uniform flow velocity at the outlet of the nozzle. Details about the evolutionary algorithm used and the CFD studies can be found in Englebrecht 4 . The profiles of the original and the optimized shape nozzles are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective function for the shape optimization was to obtain a uniform flow velocity at the outlet of the nozzle. Details about the evolutionary algorithm used and the CFD studies can be found in Englebrecht 4 . The profiles of the original and the optimized shape nozzles are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Velocity Field Data collection and analysis similar to that performed for the original (baseline) nozzle in the previous section has also been performed on the best design nozzle obtained from the results of applying the evolutionary algorithm from Englebrecht 4 . The first nine singular values corresponding to the velocity magnitude of the ensemble matrix are shown in Table (2).…”
Section: Optimal Shape Nozzlementioning
confidence: 99%
“…In scientific and practical works [8][9][10][11][12], various designs of jet mixers are presented, which can be used in the production of sweet non-alcoholic drinks.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…In the case of the real-valued problem in nine dimensions, the number of different solutions was increased by a factor of 9.6. When applied to a real world application of the sprayer nozzle (Engelbrecht, 2007), three times as many solutions were found despite using a small population size. These results support the theory that GBEAs enhance diversity in an evolving population.…”
Section: Takeover Time Experiments Resultsmentioning
confidence: 99%